Emerging Structural Patterns Within Multinational Corporations: Toward Process-Based Structures - Malnight, Thomas W. (Academy of Management Journal, 2001)
This study investigated the nature and extent of organizational change in the context of globalization through a longitudinal matched-pair analysis of two leading pharmaceutical companies. The structures of common processes in each firm were empirically characterized over time. Findings suggest that MNCs respond to complex global competitive environments by increasing internal structural complexity, a systematically differentiated structural response to relevant process subenvironments. Though supporting the existence of characteristics associated with projected MNC models, the study showed systematic variations in these characteristics across internal structures.